Violence Against Female Adolescents in Low- and Middle-Income Countries: Evidence From 36 National Household Surveys - Wilson, Nicholas L. (Journal of interpersonal violence, 2021)
The goal of this article is to provide evidence on the past-year prevalence of violence against female adolescent children age 15 to 17 and test the hypothesis that higher socioeconomic status is associated with lower likelihoods of past-year violence. We used national household surveys from 36 low- and-middle-income countries to provide evidence on the prevalence of violence against 34,901 adolescents age 15 to 17 and logistic regression analysis to measure the association between socioeconomic status and past-year violence against adolescents. Among the sample population, prevalence of physical violence by nonpartners was 10.4% and by partners was 2.8%. Prevalence of sexual violence by nonpartners was 1.8% and by partners was 1.2%. Logistic regression analysis adjusted for country of residence, and demographic characteristics indicated that completing primary school was associated with higher likelihood of physical violence by nonpartner (odds ratio [OR] = 1.13, confidence interval [CI] [1.03, 1.24]) and lower likelihoods of sexual violence by nonpartner (OR = 0.66, CI [0.53, 0.83]), physical violence by partner (OR = 0.59, CI [0.49, 0.70]), and sexual violence by partner (OR = 0.48, CI [0.36, 0.63]). Total consumer durables owned was associated with reduced likelihoods of physical violence by nonpartner (OR = 0.96, CI [0.94, 0.98]), by partner (OR = 0.88, CI [0.84, 0.93]), and sexual violence by partner (OR = 0.91, CI [0.85, 0.99]). Overall, violence against adolescents as reported in the past-year experience of females age 15 to 17 is common. Primary school completion and household wealth may convey protective benefits against violence.